Market food environments and child nutrition - Vivien Huelsen; Makaiko Khonje; Matin Qaim (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Child malnutrition and low-quality diets remain widespread public health problems in sub-Saharan Africa. Providing access to nutritious and healthy foods for all is key, but it is not at all clear how this can be achieved in various local contexts. Here, we analyze the role of markets and food environments for child diets and nutrition in Malawi along an urban-rural continuum. We develop a new methodology to characterize food environments in terms of the variety of fresh and processed foods available in local market settings. Geocoded data of market food variety are combined with individual-level child diet and anthropometric data collected through a household survey. We find large differences in food environments and diet and nutrition outcomes between urban, rural, and remote locations. The spatially-explicit analysis shows that market food variety is positively associated with child dietary diversity and negatively associated with child stunting, even after controlling for household wealth, own farm production, and other confounding factors. Our findings stress the importance of improving the functioning of markets for nutritious foods, especially in rural areas. Conceptually, we add novelty to the literature on measuring food environments.
Keywords: F63; I15; Q18; 330; Food diversity; Remoteness; Malnutrition; Processed foods; Malawi